2012
DOI: 10.1111/j.1461-0248.2012.01775.x
|View full text |Cite
|
Sign up to set email alerts
|

Fertile forests produce biomass more efficiently

Abstract: Trees with sufficient nutrition are known to allocate carbon preferentially to aboveground plant parts. Our global study of 49 forests revealed an even more fundamental carbon allocation response to nutrient availability: forests with high-nutrient availability use 58 ± 3% (mean ± SE; 17 forests) of their photosynthates for plant biomass production (BP), while forests with low-nutrient availability only convert 42 ± 2% (mean ± SE; 19 forests) of annual photosynthates to biomass. This nutrient effect largely ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
313
8

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(356 citation statements)
references
References 46 publications
24
313
8
Order By: Relevance
“…The same has not yet been done for NPP and biomass growth. But the least-cost hypothesis also makes explicit predictions about respiration costs; together with recent findings of general relationships between carbon use efficiency and soil nutrient status (Vicca et al, 2012;Fernández-Martínez, 2014), these predictions are likely to provide the basis for an equally general model of NPP. Figure 6 presents a view of what next-generation LSMs might look like.…”
Section: C Prentice Et Al: Next-generation Land-surface Modellinmentioning
confidence: 99%
“…The same has not yet been done for NPP and biomass growth. But the least-cost hypothesis also makes explicit predictions about respiration costs; together with recent findings of general relationships between carbon use efficiency and soil nutrient status (Vicca et al, 2012;Fernández-Martínez, 2014), these predictions are likely to provide the basis for an equally general model of NPP. Figure 6 presents a view of what next-generation LSMs might look like.…”
Section: C Prentice Et Al: Next-generation Land-surface Modellinmentioning
confidence: 99%
“…It is estimated that 10 to 50% of assimilated carbon is respired by the roots, with greater fractions being respired during nutrient shortage (Werf and Nagel, 1996). Vicca et al (2012) estimated that nutrient-limited forests allocate 20% more of their annual photosynthates to root symbionts than fertile forests possibly favouring the efficient acquisition and uptake of nutrients. Other studies have shown that plant growth rates under sub-optimal nutrient supply are usually enhanced by high [CO 2 ] during early growth stages (Pal et al, 2005;Pandey et al, 2015), but these enhanced growth rates cannot be sustained…”
Section: Introductionmentioning
confidence: 99%
“…The importance of site quality effects on forest growth is widely recognized in traditional forest research (McLeod and Running, 1988;Milner, 1992;Pietrzykowski, 2014;Vose and Allen, 1988) as well as in recent studies on the C allocation within forest stands (e.g. Vicca et al, 2012). Our study further highlights the need to account for differences in site quality when assessing forest C and GHG balances across forest ecosystems and to improve their up-scaling beyond ecosystem boundaries.…”
Section: Site Quality Effect On the Cumulative Nepmentioning
confidence: 79%
“…For instance, a small difference in RA R despite manifold changes in fine root biomass among the four stands was observed. This might have resulted from (i) a temporal mismatch in measurements (fine root biomass was determined in 2004 when seedling trees at the youngest site were only 2 years old, whereas root respiration was also estimated during the subsequent years (2004)(2005)(2006)(2007)(2008) of rapid tree seedling and herbaceous ground cover development), (ii) a masking effect from greater understorey and/or groundcover root respiration at the youngest and oldest stands and (iii) contrasting patterns in the allocation of assimilates from the canopy to the roots in the high-vs. low-productivity stands (Vicca et al, 2012). Thus, this observation indicates some limitations to inferring C fluxes solely from the magnitude of the biomass pools.…”
Section: Site Quality Effect On the Cumulative Nepmentioning
confidence: 89%
See 1 more Smart Citation